نقوش کے مکاتیب نمبر میں ادیبوں کےامراض - Salma; Dr Sattar Khattak (Khayaban - خیابان, 2022)
ABSTRACT: In 1957, Makateeb no of Naqoosh Lahore was published in 2 volumes. Thousands of Makateeb by 155 great writers have been published in this special issue. We can get numerous educational, literary and informative benefits from Makateeb and letters. Old Makateeb were valued because of that historical and autobiographical material which is obtained0 from Makateeb and Letters. Makateeb by great writers are significant from various aspects. This research article presents a comprehensive understanding of Makateeb no published in Naqoosh Lahore by those writers who described their own or family illnesses.